Exploring Live Selling in Social Commerce: A Systematic Review of Engagement Metrics and Sales Methods - Cahya Kamila, Fanisa Ayu; Dwiyanti Utomo, Regina (Universitas Negeri Surabaya, 2025)
Live selling has emerged as a transformative strategy within e-commerce, combining real-time interaction, entertainment, and social engagement to create a dynamic shopping experience. By integrating live video streaming with interactive elements such as product demonstrations, Q&A sessions, and viewer engagement, live selling has redefined the traditional shopping model. This study adopts a systematic literature review methodology, guided by PRISMA protocols, to explore the interplay between sales approaches and engagement metrics in live selling. The findings highlight that effective sales strategies in live selling include scarcity-driven promotions, interactive storytelling, and gamification, which drive immediacy and customer trust. Engagement metrics such as viewer retention rates, likes, comments, shares, and conversion rates are critical indicators of campaign success. These metrics not only measure audience interaction but also predict behavioral outcomes like purchase intent and customer loyalty. Furthermore, this review synthesizes evidence showing that real-time interaction enhances transparency and social proof, while urgency-based techniques amplify impulse purchases. The study also identifies gaps in regional adaptations and longitudinal effects, emphasizing the need for culturally specific research and long-term impact assessments. By bridging theoretical frameworks and practical applications, this research offers actionable insights for e-commerce practitioners aiming to optimize their live-selling strategies and academics seeking to advance knowledge in this evolving field. The results underscore live selling's potential to reshape consumer behavior and drive growth in the digital commerce ecosystem.